Effect of Jet Inclination Angle and Hole Exit Shape on Vortical Flow Structures in Low-Reynolds Number Jet in Cross-Flow. (2nd September 2012) - Yao, Yufeng; Maidi, Mohamad; Yao, Jun
Abstract : Numerical studies have been performed to visualize vortical flow structures emerged from jet cross-flow interactions. A single square jet issuing perpendicularly into a cross-flow was simulated first, followed by two additional scenarios, that is, inclined square jet at angles of 30° and 60° and round and elliptic jets at an angle of 90°, respectively. The simulation considers a jet to cross-flow velocity ratio of 2.5 and a Reynolds number of 225, based on the free-stream flow quantities and the jet exit width in case of square jet or minor axis length in case of elliptic jet. For the single square jet, the vortical flow structures simulated are in good qualitative agreement with the findings by other researchers. Further analysis reveals that the jet penetrates deeper into the cross-flow field for the normal jet, and the decrease of the jet inclination angle weakens the cross-flow entrainment in the near-wake region. For both noncircular and circular jet hole shapes, the flow field in the vicinity of the jet exit has been dominated by large-scale dynamic flow structures and it was found that the elliptic jet hole geometry has maximum "lifted-off" effect among three hole configurations studied. This finding is also in good qualitative agreement with existing experimental observations.